PERLINDUNGAN HUKUM BAGI NARAPIDANA KELOMPOK RENTAN YANG MENGALAMI KEKERASAN DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Arisandi, Muhammad Reza (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study examines the legal protection for inmates experiencing violence within correctional facilities, highlighting the critical need for effective measures to safeguard their rights. The urgency of this research arises from the alarming rates of violence reported in prisons, which undermine rehabilitation efforts and violate human rights. Utilizing a qualitative approach, data were collected through interviews with inmates, correctional officers, and legal experts. The findings reveal significant gaps in existing legal frameworks and enforcement mechanisms, suggesting that current protections are inadequate. The study concludes that comprehensive reforms are necessary to enhance legal protections for inmates, ensuring their safety and dignity while promoting a more humane correctional system.Keywords: legal protection; inmates; violence; correctional facilities; human rights.